(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
There has been much research done on energy harvesting by capturing vibration from low frequency energy. In essence, an array of piezoelectric connections is used to convert kinetic energy into electrical energy in order to produce low frequency energy. This paper presents an investigation on vibration energy harvesting which compares the performances of array piezoelectric connection. This research utilized maximum three pieces of circular piezoelectric sensor which adequate to test the combinations of array connection. Selection of the piezoelectric sensor array are series, parallel, series-parallel, parallel-series and overlapping. The observation is finding the highest power output between array piezoelectric connections. The result show that 3P piezoelectric connection obtained a higher power output among the other types of array piezoelectric which was 3.12 mW.